Pembelajaran Hermeneutik dan Teologi Sistematis tentang Kerajaan Allah: Dasar Teologis dalam Pemuridan berbasis IPTEK (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This study examines the integration of hermeneutic learning and systematic theology in science-based discipleship based on the concept of the Kingdom of God. The background of this research is the gap between the theological understanding of the Kingdom of God and the practice of digital discipleship which tends to be pragmatic and lacks a strong doctrinal foundation. This study uses mixed methods with a sequential explanatory design, which combines a survey of 50 respondents from pastors, lecturers, teachers, and students, as well as in-depth interviews to strengthen quantitative findings. The results of the study showed a very positive response to the integration of the values of the Kingdom of God and the use of science and technology in discipleship, especially in the aspects of digital ethics, love, responsibility, and the formation of Christian character. However, the understanding of hermeneutics and systematic theology still needs to be strengthened so that theological depth is not reduced by digital media and rapid technological flows. This research produces an integrative conceptual model of digital discipleship based on the Kingdom of God that combines hermeneutics as the basis for biblical interpretation, systematic theology as a doctrinal framework, and science and technology as a means of contextual and sustainable faith transformation.